Muscle Wasting Diseases: Novel Targets and Treatments - Furrer, Regula (Annu Rev Pharmacol Toxicol, 2019)
Adequate skeletal muscle plasticity is an essential element for our well-being. Inversely, compromised muscle function can drastically affect quality of life, morbidity and mortality. Surprisingly however, skeletal muscle remains one of the most under-medicated organs. Accordingly, interventions in muscle diseases are scarce, not only in neuromuscular dystrophies, but also in highly prevalent secondary wasting pathologies such as sarcopenia and cachexia. Even in other diseases that exhibit a well-established risk correlation with a sedentary life-style and exercise, e.g. type 2 diabetes or cardiovascular pathologies, current treatments are mostly targeted on non-muscle tissues. In recent years, a renewed focus on skeletal muscle has led to the discovery of various novel drug targets and the design of new pharmacological approaches. This review will provide an overview of the current knowledge of the key mechanisms involved in muscle wasting conditions, and novel pharmacological avenues that could ameliorate muscle diseases.